ANALISIS TINDAK TUTUR DIREKTIF DALAM NASKAH KABALE UND LIEBE KRYA FRIEDRICH SCHILLER - ADELIA, PUTRI (UNIVERSITAS NEGERI SURABAYA, 2017)
Language has an important function for humans to communicate. In communicating there is a speech act. According to Yule (2006: 82) speech acts are acts which displayed through speech. Speech acts divided into three types, locutions, illocution and perlocution. This research it is about illocutionary speech acts. Speech acts also happens in spoken communication (verbal) and can be shown through literary works, one of which is a drama. This research will be examined conversations between characters of the drama Kabale und Liebe by Friedrich Schiller, there are Präsident, Ferdinand, Luise, and Wurm. The drama was published in 1784 in Frankfurt.Therefore, the problem in this research are (1) how the illocution directive speech act are spoken by the characters. Then the aims of this research are (1) describe how the illocuttion directive  speech act  are spoken by the characters in drama Kabale und Liebe script by Friedrich Schiller. This research use the pragmatic illocution speech act theorie by Searle. He divided illocution speech act into five types. There are representative, directive, commissive, expressive, and declarations. The methods used in this research descriptive qualitative. And the source for this research is the drama Kabale und Liebe script by Friedrich Schiller. The data are taken from the dialog which contain speech spoken by Präsident, Ferdinant, Luise dan Wurm. Keywords: Illocution, Act, Drama